Ceftibuten-polymyxin B combination alters resistance and cell wall gene expression in multidrug-resistant Klebsiella pneumoniae - Mariana Carvalho Sturaro; Ruana Carolina Cabral da Silva; Simone Simionatto (PLoS ONE, 2026)
Background Multidrug-resistant Klebsiella pneumoniae , including carbapenem- and polymyxin-resistant strains, poses a major public health threat by severely limiting therapeutic options. Although ceftibuten (CTB) and polymyxin B (PMB) show evidence of synergistic activity, their mechanisms of action remain unclear. In this context, this study evaluated the combined effect of CTB and PMB on the expression of genes involved in cell wall synthesis and antimicrobial resistance in K. pneumoniae . Methods Protein sequences of selected resistance- and cell wall-related genes were retrieved from UniProt and analyzed in silico for conserved domains, motifs, localization (PSORTb), and pathways (KEGG). The effects of CTB/PMB, alone and in combination, were evaluated on the expression of genes involved in cell wall synthesis regulation ( ftsL, dacA, and dacC ) and antimicrobial resistance mechanisms ( pagP, pagL, ampC) . The 16s gene was used as endogenous control. Bacterial cultures (1.5 × 10 6 CFU/mL) were incubated with CTB/PMB, PMB and CTB at 0.5× and 1 × minimum inhibitory concentrations (MIC) for 2 and 4 h, followed by mRNA extraction and gene expression analysis through qRT-PCR. Results In silico analyses revealed that pagP and pagL contain conserved domains associated with lipid A modification, while ampC and ftsL showed class C β-lactamase domains. DacA and dacC were linked to the PRK13482 domain of the cl44310 superfamily. Predicted localizations placed pagP/pagL in the outer membrane, ampC in the periplasm, and ftsL/dacA/dacC in the cytoplasmic membrane. KEGG annotation indicated that ftsI , dacC , ampC , and rtxB participate in essential pathways, including peptidoglycan biosynthesis and β-lactam resistance, highlighting their physiological and clinical relevance in K. pneumoniae . After 2 h of exposure, no significant changes were observed in the expression of the selected genes. However, after 4 h, dacA, ftsL, and pagP expression levels significantly increased in all groups treated with CTB/PMB. Additionally, dacC and pagL expression were upregulated in the group treated with the combination at 1 × MIC. Conclusions Thus, combined CTB/PMB exposure was associated with modulation of gene expression involved in cell wall synthesis and antimicrobial resistance, suggesting transcriptional adaptive responses under antimicrobial pressure. These findings provide preliminary molecular insights into the response of multidrug-resistant K. pneumoniae to CTB/PMB exposure.